Perancangan Visual Ilustrasi Pada Buku Novel “Mahakurawa 1: Cakra Manggilingan” - Saputra, Mohammad Algie Eka; Pratiwi, Wilsa (Anggada : Jurnal Desain dan Seni, 2020)
Mahakurawa is a novel that tells the epic of Mahabharata through Kurawa's perspective. Mahakurawa questioned what is right and what is evil and who is the real winner of Bharatayuda. Mahabharata teaches a lot of human values in it. The values contained in the Mahabharata story are at least sufficient to be learned and understood. A modern problem relevant to this is the lack of interest in reading Indonesian youth. Efforts to increase reading interest in the younger generation are the need for a medium that can visualize physical concepts. The main purpose of visual illustration design for the novel "Mahakurawa: Cakra Malingingan" is as a communication medium that is packaged by visualizing the narrative of the story contained in the novel in order to clarify the content and meaning of the story. It is hoped that the visual illustration works that complement the novel "Mahakurawa: Cakra Manggilingan" can make it easier for readers to understand and learn the values of stories and culture contained in the novel's book.